Comparison of extraction and work up techniques for analysis of core and intact polar tetraether lipids from sedimentary environments - Lengger, Sabine; Hopmans, E.; Damste, S.; Schouten, S. (Pergamon, 2012)
Glycerol dibiphytanyl glycerol tetraether-based intact polar lipids (IPL GDGTs) are used as biomarkers for living Archaea and are analyzed utilizing a variety of extraction and quantification techniques. Most IPL GDGT studies have used a modified Bligh–Dyer extraction method, but it has been suggested that Soxhlet extraction may be more efficient for environmental samples and biomass. We investigated the impact of three different extractions (Soxhlet, Bligh–Dyer and accelerated solvent extraction, ASE), two IPL quantification methods and two work up techniques (Na2SO4 and SiO2 column) on the amount and distribution of CL (core lipid)- and IPL-derived GDGTs and crenarchaeol-based IPLs in marine sediments from the Arabian Sea and Icelandic shelf, as well as a microbial mat from a Dutch beach. The different extraction procedures gave a similar yield of CL- and IPL-derived GDGTs. Direct analysis of crenarchaeol IPLs showed, however, that, while GDGTs with a monohexose head group were not affected by the extraction method, there was a large effect on IPL GDGTs containing dihexose or hexose, phosphohexose head groups. Quantification of IPL-derived GDGTs by way of either separation over a silica column or by subtraction of CL GDGTs in the total lipid extract before and after hydrolysis gave similar results, butthe ‘subtraction-method’ had a relatively large quantification error. However, the silica column, as wellas drying over a Na2SO4 column, resulted in a loss of the hexose, phosphohexose IPLs by up to 80%.Based on the results, a modified Bligh–Dyer extraction with as little further treatment as possible isrecommended to allow measurement of the full range of IPL GDGTs in sediments.